Genogroup-Specific Multiplex Reverse Transcriptase Loop-Mediated Isothermal Amplification Assay for Point-of-Care Detection of Norovirus - Wahedul Karim Ansari; Mi-Ran Seo; Yeun-Jun Chung (Diagnostics)
Background/Objectives: Norovirus is a major cause of acute gastroenteritis worldwide. Considering its highly infectious and transmissible nature, rapid and accurate diagnostic tools are of utmost importance for the effective control of outbreaks in the context of point-of-care testing (POCT). In this study, we developed a genogroup-specific multiplex reverse transcriptase loop-mediated isothermal amplification assay to detect the human norovirus genogroups I and II (GI and GII, respectively). Methods: For the comprehensive detection of clinically relevant genotypes, two sets of primers were incorporated into the assays targeting the RdRp-VP1 junction: one against GI.1 and GI.3, and the other for GII.2 and GII.4. Following optimization of the reaction variables, we standardized the reaction conditions at 65 °C with 6 mM MgSO4, 1.4 mM dNTPs, 7.5 U WarmStart RTx Reverse Transcriptase, and Bst DNA polymerase at 8 U and 10 U for GI and GII, respectively. Amplification was monitored in real-time using a thermocycler platform to ensure precise quantification and detection. Finally, the assay was evaluated through portable isothermal detection device to test its feasibility in on-site settings. Results: Both assays detected the template down to 102–103 copies per reaction and showed high target selectivity, yielding no non-specific amplification across 39 enteric pathogens. These assays enabled prompt detection of GI within 10–12 min and of GII within 12–17 min after the reaction was initiated. Onsite validation reveals all template detection below 15 min, demonstrating its potential feasibility in point-of-care applications. Including the sample preparation time, test results were obtained in less than 1 h. Conclusions: This method is a rapid, reliable, and scalable solution for detecting human norovirus in POCT settings for both clinical diagnosis and public health surveillance.